Achieving simplified disease activity index remission in patients with active rheumatoid arthritis is associated with subsequent good functional and structural outcomes in a real-world clinical setting under a treat-to-target strategy. Issue 5 (3rd September 2017) - Hirano, Fumio; Yokoyama, Waka; Yamazaki, Hayato; Amano, Koichi; Kawakami, Atsushi; Hayashi, Taichi; Tamura, Naoto; Yasuda, Shinsuke; Dobashi, Hiroaki; Fujii, Takao; Ito, Satoshi; Kaneko, Yuko; et al.
Abstract: Objective: To verify predictive validity of simplified disease activity index (SDAI) remission for subsequent functional and structural outcomes in real-world clinical settings under a treat-to-target strategy (T2T). Methods: In this multicenter, prospective cohort study, T2T was implemented in rheumatoid arthritis (RA) patients with moderate-to-high disease activity. SDAI or clinical disease activity index (CDAI) was assessed every 12 weeks, and treatment was adjusted to achieve clinical remission or low disease activity (LDA). Multivariate logistic regression models were used to examine the associations of SDAI remission (≤3.3) at week 24 with the health assessment questionnaire-disability index (HAQ-DI) ≤ 0.5 or with the delta van der Heijde-modified total Sharp score (ΔvdH-mTSS) <smallest detectable change (SDC) at week 72. Results: Of 318 patients enrolled, 271 completed the follow-up for 72 weeks and were subjects of the analyses. Factors [odds ratio (95% confidence interval)] significantly associated with the HAQ-DI ≤0.5 were SDAI remission at week 24 [2.99 (1.42–6.28), p  = 0.004], baseline HAQ-DI [0.28 (0.18–0.45), p  = 1.3 × 10 −7 ], and baseline vdH-mTSS [0.986 (0.976–0.996), p  = 0.009]. A factor associated with ΔvdH-mTSS < SDC was SDAI remission at week 24 [3.53 (1.62–7.71), p  = 0.002]. Conclusion: Predictive validity of SDAI remission for good outcomes was verified in a T2T-implementing cohort in the current clinical settings.